Industry Beta Coefficients in the CEE Region - Nguyen, Truong Anh; Jablonský, Petr; Dvořák, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
The master thesis deals with the investigation of industry beta coefficients in the region of Central and Eastern Europe. The aim of the work is to examine how the choice of variables such as interval, periodicity and market index affect the resulting size of these coefficients. And further how these variables are perceived for different industries within the region. For the purposes of determining the size of the beta coefficients, statistical methods of linear regression were used, and estimates were made by the method of least squares, respectively FE and FD methods. All in accordance with econometric theory.
Vedoucí práce: Petr Jablonský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses